Elaboración de tejas con residuos de neumáticos y PET reciclados para viviendas en Guayaquil - Alvarado Zambrano, Ana Gabriela (2022)
This research work is based on the creation of a roof tile prototype for home in Guayaquil, having as materials, recycled rubber from disused tires and Pet. In a globalized world, incorporating recycled materials into the creation of new elements that can be used in the construction sector is an important factor in helping the environment, as well as being sources of possible jobs through entrepreneurships that can be carried out with the help of loans at low cost or with support from universities........